Molecular causality in the advent of foundation models - Lobentanzer, Sebastian; Rodriguez Mier, Pablo; Bauer, Stefan; Sáez Rodríguez, Julio (Molecular systems biology, 2024)
Correlation is not causation: this simple and uncontroversial statement has far-reaching implications. Defining and applying causality in biomedical research has posed significant challenges to the scientific community. In this perspective, we attempt to connect the partly disparate fields of systems biology, causal reasoning, and machine learning to inform future approaches in the field of systems biology and molecular medicine.